2019
DOI: 10.1007/s00249-019-01389-w
|View full text |Cite
|
Sign up to set email alerts
|

57Fe enrichment in mice for β-thalassaemia studies via Mössbauer spectroscopy of blood samples

Abstract: In this work, wild-type and heterozygous β-thalassaemic mice were enriched with 57 Fe through gastrointestinal absorption to characterize in more details the iron complexes appeared in the measured Mössbauer spectra. The 57 Fe enrichment method was validated and Mössbauer spectra were obtained at 80K from blood samples from wild-type and β-thalassaemic mice at 1, 3, 6, and 9 months of age. As expected, the haemoglobin levels of the thalassaemic mice were lower than from normal mice indicating anaemia. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…127 Importantly, absorption is directly correlated to concentration, so the relative ratios of resonant nuclei can be discerned. Limitations of the technique include the need for 57 Fe labelled samples to absorb the c-rays emitted from the 57 Co source, [128][129][130] and the need to either work with frozen samples at low temperatures or with precipitated complexes at higher temperature, i.e., the sample must be in the solid state to exploit the Mössbauer effect. If not in the solid state, nuclear recoil experienced by the emitting 57 Co and absorbing 57 Fe nuclei leads to energy loss and decreased absorption.…”
Section: Epr Spectroscopymentioning
confidence: 99%
“…127 Importantly, absorption is directly correlated to concentration, so the relative ratios of resonant nuclei can be discerned. Limitations of the technique include the need for 57 Fe labelled samples to absorb the c-rays emitted from the 57 Co source, [128][129][130] and the need to either work with frozen samples at low temperatures or with precipitated complexes at higher temperature, i.e., the sample must be in the solid state to exploit the Mössbauer effect. If not in the solid state, nuclear recoil experienced by the emitting 57 Co and absorbing 57 Fe nuclei leads to energy loss and decreased absorption.…”
Section: Epr Spectroscopymentioning
confidence: 99%
“…For the purposes of this study, wild-type C57BL/6, and heterozygous thalassaemic (th3/+) mice were raised and enriched with 57 Fe as described in Charitou et al [15]. Due to the fact that MS measurements of bio-samples are time-consuming and also that the 57 Fe isotope used for enrichment is fairly expensive, only one sample per group (th/3+ and wild-type) and age (1, 3, 6, 9 months) could be prepared and studied.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…In a previous work [14], we demonstrated that the thalassaemic mouse model is a good candidate to study thalassaemia by means of Mössbauer spectroscopy. Subsequently, heterozygous thalassaemic (th3/+) and wild-type (C57BL/6) mice were enriched with Fe 57 [15] via gastrointestinal absorption to increase the statistics of the spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic CEMS spectra were fitted with a discrete distribution of hyperfine fields B hf with a least-squares procedure [36]. A correlation between hyperfine field and isomer shift δ was used to take into account the Fe environment distribution [37][38][39][40]. δ values at the 57 Fe nuclei are given relative to α-Fe at room temperature.…”
Section: Introductionmentioning
confidence: 99%